PENGARUH VARIASI KUAT ARUS LISTRIK DAN WAKTU PROSES ELECTROPLATING TERHADAP KEKUATAN TARIK, KEKERASAN DAN KETEBALAN LAPISAN PADA BAJA KARBON RENDAH DENGAN KROM - Arif Surya Darmawan D.P; I Dewa Ketut Okariawan; Nasmi Herlina Sari (Universitas Mataram, 2015)
The usage of carbon steel at present is growing rapidly. The carbon steel is commonly used in the machining appliance and material construction, as well as oil or gas piping. Improvement of physical properties of steel can be performed by electroplating. The goal of this research was to prove the influence variation of strong electric current and processing time electroplating tensile strength, hardness and layer thickness on low carbon steel with chrome. The benefits of this research is to gain the information about a strong in fluence of electric current and time again sthardness and thickness of thetensile strength of low carbon steel with chrome plating.This research using low carbon steel coated by electroplating method with variations strong electric current 17.8A, 22.7A and 27.3A, and the length of processing 5, 10, and 15 minutes. The type of testing which done are to test the thickness, the hardness and tensile test. The processing of data were analyzed using analysis of variance two-way.Thickness layer of chrome increased along with increasing strong currents and the length of time coating. The highest value of the thickness chrome layer with strong currents occur in the calculation of 27.3A and with in 15 minutes of 0.00015 as well as microscope observation of 0.483 where there is a difference between calculation and observation microscope 400X magnification ranges from 99.9%. The highest hardness values obtained with strong currents 27,3A and within 15 minutes of 23,58 VHN or 12,621% harder compare with raw materials. For tensile test itself was increasing tensile strength with the highest value of 627.8 N / mm2 or 6.65% more than raw material.